Governing Future Radicals in Europe. Issue 2 (14th September 2012) - de Goede, Marieke; Simon, Stephanie
<x xml:space="preserve">Abstract</x> Abstract: This article analyses European initiatives to counter radicalisation and recru‐itment as a practice of governing that works preemptively through civil society and semi‐public spaces. Since the London and Madrid bombings, the EU agenda in this domain is substantial and ambitious. At the same time, proposals are embraced by member states to various degrees and materialise in local settings and concrete programmes in different ways. We propose to regard radicalisation as an assemblage of governing that is mobilised through particular threat representations, knowledge practices, training programmes and strategies for intervention. This lens allows for the simultaneous recognition of national differentiations, the power and reach of "Europe", and the tensions, fluid relations and alignments that are forged in counter‐radicalisation conceptualisation and practice. In so doing, the motivation behind our research is to make strange the idea of radicalisation itself, which has been fully embraced and mobilised as a problem of governance across Europe.